Implementasi Kebijakan Pencegahan Pencemaran Air Permukaan oleh Air Limbah Industri di Daerah Aliran Sungai Brantas Kediri - Reny Nugraheni; Ekawati Wasis Wijayati (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
The City Government of Kediri in an effort to preserve the environment forms a legal basis namely the City Regulation of Kediri Number 3 of 2009 cocerning Environmental Management. One of the targets in the regional regulation is to preserve the watershed and water sources. In accordance with the 2015-2019 Medium Term Development Plant , there are 15 watersheds that are prioritized to be restored first and one of them is the Brantas watersheds. This study aims to identify the implementation of the Kediri City Government policy in preventing surface water pollution by industrial wastewater in the Brantas River Basin, Kediri District. The method used in this research is descriptive. Collecting data by conducting in-depth interviews with industrial waste water treatment officers and officers in the field of environmental damage pollution in the Departement of Environment, Hygiene and Gardening of Kediri City. Based on the research results, it is known that most of the industries have carried out wastewater treatment and not ith a dilution process and most of the industries have IPLC. Based on the wuality standards, it is known that the quality standards of industrial waste are in accordance with the standards set by the government and the industry routinely conducts wastewater quality tests, but the industry is still lacking in reporting the results of wastewater quality tests. In wastewater treatment facilities and infrastructure, the government has provided rubbish place for industrial estates and most industries have their own rubbish place.